Greater Adherence to Life's Simple 7 Is Associated With Less Arterial Stiffness: the Atherosclerosis Risk in Communities (ARIC) Study. (26th April 2019) - Oyenuga, Abayomi O; Folsom, Aaron R; Cheng, Susan; Tanaka, Hirofumi; Meyer, Michelle L
Abstract: Background: Greater arterial stiffness is associated independently with increased cardiovascular disease risk. The American Heart Association (AHA) has recommended following "Life's Simple 7 (LS7)" to optimize cardiovascular health; we tested whether better LS7 in middle age is associated with less arterial stiffness in later life. Methods: We studied 4, 232 black and white participants aged 45–64 years at the baseline (1987–89) visit of the Atherosclerosis Risk in Communities Study cohort who also had arterial stiffness measured in 2011–13 (mean ± SD interval: 23.6 ± 1.0 years). We calculated a 14-point summary score for baseline LS7 and classified participants as having "poor" (0–4), "average" (5–9), or "ideal" (10–14) cardiovascular health. We used logistic regression to calculate odds ratios (ORs) and 95% confidence intervals (95% CI) for arterial stiffening: a high carotid-femoral pulse wave velocity (cfPWV, ≥13.23 m/s) or a high central pulse pressure (central PP, ≥ 82.35 mm Hg). Results: The age, race, sex, and heart rate-adjusted ORs (95% CI) for high cfPWV in the "ideal, " "average, " and "poor" LS7 summary categories were 1 (Reference), 1.30 (1.11, 1.53), and 1.68 (1.10, 2.56), respectively ( P -trend = 0.0003). Similarly, the adjusted ORs (95% CI) for high central PP across LS7 summary categories were 1 (Reference), 1.48 (1.27, 1.74), and 1.63 (1.04, 2.56), respectively ( P -trend <0.0001). Conclusion: Greater LS7 score in middle age is associated with less arterial stiffness 2–3 decades later. These findings further support the AHA recommendation to follow LS7 for cardiovascular disease prevention.